Crisis and hypercalcemic primary hyperparathyroidism - Loja Oropeza, David (2001)
We present a 45 year old female with long standing primary hiperparathyroidism due to parathyroid adenoma. Initially she had nephrolithiasis and obstinate constipation, and then neuromuscular features and bone illness consisting of osteitis fibrosa cystica, osteoporosis and pathological fracture. She was admitted for acute pancreatitis associated to hypercalcemic crisis that remitted. After parathyroidectomy the patient developed the "hungry bone syndrome" from which she recovered. On follow-up she presented no symptoms. We discuss the clinical course, diagnosis and therapheutics.